Pengembangan Lembar Kerja Siswa Matematika dan Fisika Berbasis Model Pembelajaran Missauri Mathematic Project Diintergasikan dengan Kearifan Lokal Siswa Dalam Pengajaran Matematika dan Fisika - Nuraina Nuraina; Muliana Muliana; Hayatun Nufus; Syarifah Rita Zahara (Postgraduate, University of Mataram, 2022)
This study was conducted to develop students’ worksheet based Missouri Mathematic Project (MMP) in teaching and learning mathematics and physics. These materials were also integrated with students’ local wisdom. To realize the construction, this research used the Analysis, Design, Development, Implementation and Development (ADDIE) as a research model. The students’ worksheet were reviewed and validated by two different experts in the aspects of media and materials used. The results indicated that 92.22% of the media was considered very valid. The materials employed in the worksheet were regarded 89.66 % to be very valid and as much as 91.52% was considered appropriate. Meanwhile, the data from questionnaires showed that the percentage evaluation as much as 77.24 % were taken from mathematics worksheet and 76.95 % was of physics. These results indicated that the students’ worksheets used to teach mathematics and physics can be applied as teaching and learning materials in the area of social arithmetic and in the unit and measurements.